Time-resolved x-ray absorption spectroscopy probe in ultrafast surface chemistry - Anders Nilsson (Structural Dynamics)
To celebrate the scientific achievement of Jo Stöhr, I present here a personal account of the use of x-ray absorption spectroscopy to probe dynamics on surfaces using x-ray lasers. In particular, I will review the investigation of ultrafast processes in adsorbates on surfaces using an optical pump and an x-ray absorption spectroscopy probe. Here, it is shown that it is possible to gain insight into the effects of electronic excitations in metals on adsorbates as well as laser-induced vibrational motions. Furthermore, the ultrafast optical pump allows the detection of the CO precursor state in the desorption channel, species close to the transition state in CO oxidation, and the transient HCO intermediate during CO hydrogenation on Ru(0001).